2007
DOI: 10.1161/circulationaha.107.719005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Testosterone and Mortality Due to All Causes, Cardiovascular Disease, and Cancer in Men

Abstract: Background-The relation between endogenous testosterone concentrations and health in men is controversial. Methods and Results-We examined the prospective relationship between endogenous testosterone concentrations and mortality due to all causes, cardiovascular disease, and cancer in a nested case-control study based on 11 606 men aged 40 to 79 years surveyed in 1993 to 1997 and followed up to 2003. Among those without prevalent cancer or cardiovascular disease, 825 men who subsequently died were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
226
4
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 683 publications
(246 citation statements)
references
References 54 publications
9
226
4
7
Order By: Relevance
“…Lower testosterone levels have been associated with increased overall and cardiovascular-related mortality in middle-aged and older men. [121][122][123] However, other studies have not shown a clear relationship between lower testosterone and higher mortality. 124,125 In the Caerphilly study, a higher ratio of cortisol to testosterone was associated with ischemic heart disease but this was attenuated after adjustment for components of the insulin-resistance syndrome.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 97%
“…Lower testosterone levels have been associated with increased overall and cardiovascular-related mortality in middle-aged and older men. [121][122][123] However, other studies have not shown a clear relationship between lower testosterone and higher mortality. 124,125 In the Caerphilly study, a higher ratio of cortisol to testosterone was associated with ischemic heart disease but this was attenuated after adjustment for components of the insulin-resistance syndrome.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 97%
“…[51][52][53][54][55][56][57][58][59] However, a 2010 meta-analysis limited to longitudinal (cohort) studies in middle-aged men found no association between endogenous TT levels and risk of CVD in middle-aged men. 60 A more recent study by Corona et al 61 found significant associations between low TT levels and high estradiol levels and CVD in a meta-analysis of 49 cross-sectional studies.…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…60 Recently, epidemiological studies have found that low testosterone levels are a predictor of all-cause and cardiovascular mortality in elderly men. 61,62 These findings were followed by studies investigating the incidence of CVD and testosterone levels. 63,64 According to these observations, endogenous testosterone appears to exert beneficial effects on the cardiovascular system.…”
Section: Association Of Low Testosterone Levels With Cvdmentioning
confidence: 99%